To compare the accuracy of 0.022 inch slot of stainless steel and ceramic orthodontic brackets marketed by different manufacturers - Perumallapalli Divya; Santosh Reddy Banswada; Shilpa Reddy Kukunuru; Keerthi B Kavya; R Ravi Rathod; Keerthi Chowdary Polavarapu (Wolters Kluwer Medknow Publications, 2021)
Aim of the Study: The aim of the present study was to analyze the accuracy of 0.022 inch slot of stainless steel and ceramic orthodontic brackets marketed by different manufacturers. Materials and Methods: An in vitro study was done on upper left central incisor bracket of MBT 0.022 slot of American orthodontics (AO), 3M Unitek, Ormco with each 20 of stainless steel and ceramic brackets divided into six groups, and the total sample was 120. The brackets were scanned with stereo microscope of Magnus Company and Image Pro plus analysis software was used to evaluate the mesial face and base, distal face and base. Results: Comparison in between the groups of stainless steel showed that 3M Unitek brackets showed higher slot widths as compared to AO and Ormco which was statistically significant (P < 0.05). Comparison in between the groups of ceramic brackets of AO brackets showed higher slot widths as compared to Ormco and 3M Unitek ceramic brackets which was statistically significant (P < 0.05). Conclusion: By this study, there was a difference between stated values and measured values of brackets displaying inaccuracies in dimension. A clear impreciseness about the appliance could be needed during the finishing and detailing stage to avoid loss of torque control due to slot oversize and the divergence of slot walls.